2014
DOI: 10.1111/bph.12635
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin inhibits the activity of acid‐sensing ion channels through the vasopressin, V1A receptor in primary sensory neurons

Abstract: BACKGROUND AND PURPOSEA growing number of studies have demonstrated that oxytocin (OT) plays an analgesic role in modulation of nociception and pain. Most work to date has focused on the central mechanisms of OT analgesia, but little is known about whether peripheral mechanisms are also involved. Acid-sensing ion channels (ASICs) are distributed in peripheral sensory neurons and participate in nociception. Here, we investigated the effects of OT on the activity of ASICs in dorsal root ganglion (DRG) neurons. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 74 publications
(116 reference statements)
6
57
1
Order By: Relevance
“…Our previous and current studies show that these characterized currents could be completely blocked by broad-spectrum ASIC channel blocker amiloride, also by ASIC3 channels blocker APETx2 (Fig. 1a) [28]. These currents were thus considered to be ASIC3-like currents and were mainly investigated in this study.…”
Section: Utp Enhanced Asic Currents In Rat Dorsal Root Ganglia Neuronsmentioning
confidence: 90%
See 1 more Smart Citation
“…Our previous and current studies show that these characterized currents could be completely blocked by broad-spectrum ASIC channel blocker amiloride, also by ASIC3 channels blocker APETx2 (Fig. 1a) [28]. These currents were thus considered to be ASIC3-like currents and were mainly investigated in this study.…”
Section: Utp Enhanced Asic Currents In Rat Dorsal Root Ganglia Neuronsmentioning
confidence: 90%
“…Most of these acid currents can be characterized by a large transient current followed by fast inactivation and then a small sustained current with no or very slow inactivation [27]. Our previous and current studies have identified that the characterized acidosis-evoked currents are mainly mediated by ASIC3, since they could be completely blocked by ASIC3 channels blocker APETx2 [28]. We thus considered them to be ASIC3-like currents, although precise ASIC subunits need to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Acting through a pathway involving nitrous oxide, oxytocin leads to a reduction in excitability of capsaicin sensitive nociceptors (Gong et al, 2015). There is evidence that oxytocin also acts through the vasopressin, V1A receptor in primary sensory neurons (Qiu et al, 2014). Interestingly activation of parvocellular PVN oxytocin secreting neurons, in addition to acting by a descending spinal pathway, also results its systemic release from the posterior pituitary by virtue of its parallel projection to the SON (Eliava et al, 2016).…”
Section: The Analgesic Effects Of Oxytocinmentioning
confidence: 99%
“…Yang et al further demonstrated a dose-dependent, enhanced analgesic effect of DN with stimulation of the supraoptic nucleus and a minimal analgesic effect when the nucleus was ablated [160]. According to Qiu et al the activation of vasopressin (V1A) receptors by oxytocin released form the posterior pituitary is thought to trigger calcineurindependent phosphorylation of ASIC channels, decreasing the amplitude of ASIC currents, acid-evoked membrane excitability, and the depolarization amplitude secondary to acid stimuli [161]. In addition, oxytocin has been shown to inhibit pain directly by binding to oxytocin receptors (OXTR) on first order sensory afferents, second order neurons and GABAergic interneurons in the spinal cord, inhibiting the transmission of pain [162].…”
Section: Asic Channelsmentioning
confidence: 99%